REKONSTRUKSI PEMAHAMAN DAN AKTIVITAS KEAGAMAAN DALAM MERESPON PENYEBARAN COVID-19 DI INDONESIA (STUDI KASUS JAMA’AH RANTING AISYIYAH DI DESA GURAH KECAMATAN GURAH KABUPATEN KEDIRI) - Heylen Amildha Yanuarita; Fauziah Hanum; Desi Tri Suryani (Universitas Kadiri, 2020)
ABSTRACT Extension activities on the understanding and implementation of religious activities inresponse to the spread of Covid-19 in the congregation of 'Aisyiyah, Gurah Village, GurahDistrict, Kediri Regency, are carried out offline and online and still comply with thegovernment's appeal by implementing health protocols. In this activity, it involved 4 membersof the Community Service team and 18 participants from the congregation of 'Aisyiyah'branches of the Village of Gurah, District of Gurah, Kediri Regency. Implementation ofcounseling begins with the delivery of material and continues with discussions in order tofind out the obstacles or inhibiting factors of carrying out religious activities online. Thenthere is material assistance for the use of applications on mobile phones such as WhatsAppin the implementation of online religious activities.Keywords:Extension, understanding and implementation of religious activities ABSTRAK Kegiatan penyuluhan tentang pemahaman dan pelaksanaan aktivitas keagamaan dalammerespon penyebaran Covid-19 pada jama’ah ranting ‘Aisyiyah Desa Gurah KecamatanGurah Kabupaten Kediri dilaksanakan secara luring dan daring tetap mematuhi himbauanpemerintah dengan menerapkan protokol kesehatan. Dalam kegiatan ini melibatkan 4 anggotatim Pengabdian kepada masyarakat dan 18 peserta jama’ah ranting ‘Aisyiyah Desa GurahKecamatan Gurah Kabupaten Kediri. Pelaksanaan penyuluhan diawali dengan penyampaianmateri dan dilanjutkan diskusi guna mengetahui kendala atau faktor penghambat daripelaksanan kegiatan keagamaan secara daring. Kemudian dilakukan pendampingan materipenggunaan aplikasi pada telepon genggam seperti WhatsApp dalam pelaksanaan kegiatankeagamaan secara daring.Kata kunci: Penyuluhan, pemahaman dan pelaksanaan aktivitas keagamaan